Newborn screening for citrin deficiency and carnitine uptake defect using second-tier molecular tests - Wang Li-Yun; Chen Nien-I; Chen Pin-Wen; Chiang Shu-Chuan; Hwu Wuh-Liang; Lee Ni-Chung; Chien Yin-Hsiu (BMC, 2013)
Abstract Background Tandem mass spectrometry (MS/MS) analysis is a powerful tool for newborn screening, and many rare inborn errors of metabolism are currently screened using MS/MS. However, the sensitivity of MS/MS screening for several inborn errors, including citrin deficiency (screened by citrulline level) and carnitine uptake defect (CUD, screened by free carnitine level), is not satisfactory. This study was conducted to determine whether a second-tier molecular test could improve the sensitivity of citrin deficiency and CUD detection without increasing the false-positive rate. Methods Three mutations in the SLC25A13 gene (for citrin deficiency) and one mutation in the SLC22A5 gene (for CUD) were analyzed in newborns who demonstrated an inconclusive primary screening result (with levels between the screening and diagnostic cutoffs). Results The results revealed that 314 of 46 699 newborns received a second-tier test for citrin deficiency, and two patients were identified; 206 of 30 237 newborns received a second-tier testing for CUD, and one patient was identified. No patients were identified using the diagnostic cutoffs. Although the incidences for citrin deficiency (1:23 350) and CUD (1:30 000) detected by screening are still lower than the incidences calculated from the mutation carrier rates, the second-tier molecular test increases the sensitivity of newborn screening for citrin deficiency and CUD without increasing the false-positive rate. Conclusions Utilizing a molecular second-tier test for citrin deficiency and carnitine transporter deficiency is feasible.